2019
DOI: 10.18178/ijiet.2019.9.10.1287
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Learning Experience Using Real-Time Cognitive Evaluation

Abstract: There is increasing evidence that learners' affective and cognitive states play a key role in the learning process. This suggests that systems which are able to detect these states can dynamically use adapted strategies to increase the pace of the learners' skill acquisition and improve their learning experience. In this work, we present a novel approach for automatically adapting the learning strategy in real-time according to the learner's detected mental state. The main goal of the approach is to maintain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Recent studies demonstrated that machine learning approaches, where a linear classifier is trained to discriminate between high and low levels of attention based on EEG features, can achieve a very high level of classification accuracy (eg, Chen et al, 2017). In a recent example, an adaptive tutoring system based on EEG measures of cognitive engagement and load had a positive impact on learning outcomes (Chaouachi et al, 2019). However, other studies reported that attention classifiers are not easily generalizable across students (Dhindsa et al, 2019) and are not predictive of how student engagement is rated by annotators (Booth et al, 2018).…”
Section: Eeg-facilitated Attention Aware Systemsmentioning
confidence: 99%
“…Recent studies demonstrated that machine learning approaches, where a linear classifier is trained to discriminate between high and low levels of attention based on EEG features, can achieve a very high level of classification accuracy (eg, Chen et al, 2017). In a recent example, an adaptive tutoring system based on EEG measures of cognitive engagement and load had a positive impact on learning outcomes (Chaouachi et al, 2019). However, other studies reported that attention classifiers are not easily generalizable across students (Dhindsa et al, 2019) and are not predictive of how student engagement is rated by annotators (Booth et al, 2018).…”
Section: Eeg-facilitated Attention Aware Systemsmentioning
confidence: 99%
“…For the workload index, if the slope value is between −0.03 and +0.03, then the workload is considered as optimal. Otherwise, if the slope value is above 0.03, the learner is considered as overloaded, and if the slope is below −0.03, the learner is considered as underloaded [91]. Moreover, if the learner is both mentally engaged and has an optimal workload, then the learner's mental state is considered positive.…”
Section: Eeg Recordingmentioning
confidence: 99%
“…40,[42][43][44]46,47,[52][53][54][55][56][57][58][59][60][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]84,86,[88][89][90][91][92]96], while the remainder (specifically 17, 21%) were conference papers…”
mentioning
confidence: 99%